Monetary Policy and Stock Price Dynamics in Nepal - Shrestha, Mani Raj (Journal of Business and Management Research, 2020)
Monetary authorities are attentive towards stock price movement because of its significance in financial stability. Though stock price is one of the major channels of monetary transmission, very little is known about it in Nepali context. This study analyzed monetary variables, stock prices, and monetary policy goals using time series data. Results from Koyck approach to distributed lags, vector autoregression and mediation analysis revealed mixed evidence of causality between monetary policy and stock prices. Though results were not consistent across different econometric analysis, inter-bank interest rate, narrow money supply, broad money supply, monetary policy announcement, and monetary policy stances were found to be significant in explaining stock prices. Furthermore, causality also existed from stock prices to monetary policy, suggesting that monetary authorities also consider development in stock prices while formulating monetary policies. However, stock prices had not been found to mediate the relationship between monetary policy variables and monetary policy goals, which questioned stock prices being a channel of monetary policy transmission in Nepal.